2020
DOI: 10.1186/s12911-020-01160-8
|View full text |Cite
|
Sign up to set email alerts
|

Staff perspectives on the usability of electronic patient records for planning and delivering dementia care in nursing homes: a multiple case study

Abstract: Background: The electronic patient record (EPR) has been introduced into nursing homes in order to facilitate documentation practices such as assessment and care planning, which play an integral role in the provision of dementia care. However, little is known about how the EPR facilitates or hinders these practices from the end-user's perspective. Therefore, the objective of this qualitative study was to explore the usability issues associated with the EPR for assessment and care planning for people with demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(88 citation statements)
references
References 46 publications
0
88
0
Order By: Relevance
“…All studies included adults with dementia, focusing specifically on requirements for people with dementia (11/29, 38%) [ 31 , 32 , 38 - 40 , 43 , 47 , 49 , 50 , 53 , 54 ] or within a mixed population (18/29, 62%) [ 33 - 37 , 41 , 42 , 44 - 46 , 48 , 51 , 52 , 55 - 59 ]. The average percentage of residents with dementia was 52.8% in the mixed population studies that reported the proportion (6/29, 21%) [ 35 , 37 , 44 , 46 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies included adults with dementia, focusing specifically on requirements for people with dementia (11/29, 38%) [ 31 , 32 , 38 - 40 , 43 , 47 , 49 , 50 , 53 , 54 ] or within a mixed population (18/29, 62%) [ 33 - 37 , 41 , 42 , 44 - 46 , 48 , 51 , 52 , 55 - 59 ]. The average percentage of residents with dementia was 52.8% in the mixed population studies that reported the proportion (6/29, 21%) [ 35 , 37 , 44 , 46 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…eHealth is at an advantage if it aligns with data and technology already in use [ 37 , 40 , 51 , 52 ]. Concerns on patient privacy and electronic transfer of confidential information act as institutional firewalls [ 40 , 49 ] but can be overcome by encrypting data and assigning residents confidential numbers [ 49 ] . A way to increase the adaptability of a device is through the provision of customizable tools such as drop-down menus [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations